Magazine "La Hormiga de Oro". Documentary Analysis - Arias Durá, Raquel (Revista General de Información y Documentación, 2014)
The journals allows as to know the political, social and cultural situation of each moment in time, the aim of this project is to carry out a study of La Hormiga de Oro catholic magazine (1884-1936). Is analyzed for the first time its development since inception, its structure, the journalist team and professional collaborators, as well as the entrepreneurial project of the great company La Hormiga de Oro, composed of the magazine, the bookshop and the print house. Additionally, the life and work of his founder Luis María de Llauder, publicist, relevant figure of the Carlism and, above all, great journalist, is also analysed.
Keywords: Catholic press; illustrated magazine; La Hormiga de Oro; Catholicism; carlism; documentary analysis